Kutukan Sumber Daya atau Katalis Kesejahteraan: Bagaimana Dampak Hilirisasi Nikel terhadap Kemiskinan di Sulawesi? - Zufarulhaq, Muhammad Syafiq; Damayati, Ashintya (Jurnal Kebijakan Ekonomi, 2025)
This study evaluates the impact of nickel downstreaming on poverty levels in Sulawesi by examining the effectiveness of smelter development and the raw ore export ban policy as resource-based industrialization strategies. The primary contribution of this research lies in its identification strategy, which employs a staggered Difference-in-Differences approach with two-way fixed effects using panel data from 54 regencies/municipalities over the period 2010–2023. The baseline regression results show that the average effect of smelters is not statistically significant in reducing poverty. On the other hand, the raw mineral export ban policy is found to significantly reduce poverty. However, there is no evidence that this policy moderates or amplifies the effect of smelters on poverty. Nevertheless, the event study results reveal that the presence of smelters has a significant and consistent negative effect on poverty rates, emerging a few years after smelters begin operating—indicating that smelters contribute to poverty reduction in the medium term (delayed benefit). Nonetheless, it does not necessarily constitute a form of maslahah.